Abstraction, ambiguity and memory in selected artworks by Ursula von Rydingsvard and Kemang wa Lehulere - Jacobs, Natasha Sandra Ruth (My University, 2017)
This research report explores the influences of memory in selected works by two visual artists: South African Kemang Wa Lehulere’s Remembering the Future of a Hole as a Verb 2.1 and Polish artist Ursula von Rydingsvard’s Droga. The report examines the ways in which personal memory can inform creative practice and the surface difficulties such endeavours may present. These works and writings on memory and creative practice inform my own practice, through which I investigate ways of expressing my memories of my grandparents’ carpentry workshop in Sunnydale Eshowe in KwaZulu Natal, South Africa.
A research report submitted to the Faculty of Humanities, University of the Witwatersrand, in partial fulfilment of the requirements for MA by Coursework and Research Report, Johannesburg, 2017
Keywords: Wa Lehulere, Kemang--1984--Exhibitions; Von Rydingsvärd, Ursula--1942--Exhibitions; Memory in art; Wood-carving--South Africa--KwaZulu-Natal--Exhibitions; Autobiographical memory in art; Art and history--South Africa--KwaZulu-Natal; Art, Modern--19th century--Exhibitions; Art, Modern--20th century--Exhibitions